Introduction to International Legal English - Krois-Linder, Amy., Matt, Firth (Cambridge Cambridge University Press, 2009)
This intermediate level course is for law students or newly-qualified lawyers who need to use English in their legal work or studies. Suitable for classroom use or self-study, the course focuses on a variety of legal topics including company law, litigation and arbitration, criminal law and comparative law.
Keywords: English Practice